The Effect Of E-Service Quality On Repurchase Interests Of The Online Shopping Shopee Indonesia - Efawati, Yen; Rifaturrahman, Rafi Fauzan; Chaniago, Harmon (Universitas Budi Luhur, 2024)
E-service quality is an essential factor influencing customers' decision to repurchase in e-commerce. In practice, many e-commerce companies cannot provide fast service when customers experience problems or have questions. Therefore, this research needs to be carried out to prove that online service quality influences repurchase interest. The quantitative descriptive method was used in this study. Furthermore, this study analyzes how e-service quality affects customers' decisions when repurchasing. Validity and reliability tests, normality tests, and simple linear regression analysis were conducted on data from 103 Bandung State Polytechnic students. Data collection is done through links in social media or G-Form. The research results show that the seven dimensions of electronic service quality significantly influence repurchase interests. This shows that raising the caliber of electronic services increases customers' desire to repurchase, particularly with Shopee Indonesia's online marketplace. This research discusses repurchase interest among vocational school students based on the quality of electronic services they perceive and confirms the seven dimensions that have been identified. This research also has implications for marketing management practices to create more innovation, especially improvements in electronic services for sustainable business continuity.